2002
DOI: 10.1001/archneur.59.10.1622
|View full text |Cite
|
Sign up to set email alerts
|

Familial Dementia With Lewy Bodies

Abstract: Familial DLB exists, although there is substantial clinical and neuropathological heterogeneity within and between families. Additional clinicopathologic and genetic studies are necessary to further our understanding of DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In some, 40-80% of patients with AD possess at least one apoE4 allele (12). Likewise, apoE4 is associated with earlier onset, progression, or severity of head trauma (13)(14)(15)(16)(17)(18)(19), stroke (20,21), complications after coronary artery bypass surgery (22,23), Parkinson's disease (24)(25)(26)(27), amyotrophic lateral sclerosis (28)(29)(30)(31)(32), multiple sclerosis (33,34), diabetic neuropathy (35), sleep apnea (36), Lewy body disorders (37), and CNS ischemia (38).…”
Section: Apoe and Neuropathologymentioning
confidence: 99%
“…In some, 40-80% of patients with AD possess at least one apoE4 allele (12). Likewise, apoE4 is associated with earlier onset, progression, or severity of head trauma (13)(14)(15)(16)(17)(18)(19), stroke (20,21), complications after coronary artery bypass surgery (22,23), Parkinson's disease (24)(25)(26)(27), amyotrophic lateral sclerosis (28)(29)(30)(31)(32), multiple sclerosis (33,34), diabetic neuropathy (35), sleep apnea (36), Lewy body disorders (37), and CNS ischemia (38).…”
Section: Apoe and Neuropathologymentioning
confidence: 99%
“…Characteristic neuropsychiatric features are not present in every patient with a specific proteinopathy. Patients with DLB not manifesting hallucinations or delusions, for example, have been described,89 and not all patients with frontotemporal dementia show disinhibition or obsessional behavior 1, 49. This heterogeneity may be explained by differing genetic backgrounds, extent of regional pathological involvement, and variations in transmitter deficits that modify the behavioral predispositions associated with the proteotype.…”
Section: Proteotype–phenotype Correlationsmentioning
confidence: 99%
“…While not conclusive, several studies have indicated an increased frequency of APOE ε4 in diffuse Lewy body disease [1,23,42], especially in association with concomitant Alzheimer type pathology [10,22]. It is of interest that familial DLB has also been shown to be associated with APOE ε4 [42,53,58]. The possibility of gene-gene interaction in families with APOE ε4 and EIF4G1 variants needs to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%